Initial Values and Income Convergence: Do “The Poor Stay Poor”? - Shioji, Etsuro (The Review of Economics and Statistics, 2004)
A panel data estimation finds a high speed of income convergence among the U.S. states. However, initial incomes show a pattern which is difficult to explain by the estimated model. A simulation study shows that this pattern can be explained much more naturally when we assume that true convergence is slow.